Eco-Tourism Village Program: The ‘Ninja Path’ Turtle Conservation Initiative to Promote Sustainable Ecotourism at Kili-Kili Beach, Wonocoyo Village, Panggul District, Trenggalek - Lintang Akbar (Prospect: Jurnal Pemberdayaan Masyarakat, 2026)
The Eco-Tourism Village Program located in Wonocoyo Village, Trenggalek Regency, East Java, is a Corporate Social Responsibility (CSR) initiative of PT Pertamina Patra Niaga Fuel Terminal Madiun. The program was implemented from 2021 to 2025, focusing on community empowerment in areas surrounding the turtle conservation site, as well as the protection and preservation of sea turtle habitats and populations in the Kili-kili Beach Turtle Conservation Area. The program has generated positive impacts in economic, environmental, and social aspects. The objective of the community empowerment activities in the Kili-kili Beach Turtle Conservation Area is to increase tourist visits to the site, thereby creating a multiplier effect in the form of economic improvement, environmental sustainability, and the enhancement of sea turtle habitats and populations in the conservation area located in Wonocoyo Village, Panggul District, Trenggalek Regency. The results of the study indicate that this empowerment program has produced positive impacts for the local community, visitors, and the Community Monitoring Group (Pokmaswas) of Kili-kili Beach. These impacts include a sea turtle egg hatching success rate of 90% and an increase in conservation-related income from the educational stall reaching IDR 13,791,500.